Full-thickness macular hole in Bartonella henselae neuroretinitis in an 11-year-old girl - Seth, Anisha (Oman J Ophthalmol, 2015)
Cat scratch disease is a febrile illness caused by Bartonella henselae and is associated with rash at the site of cat bite or scratch and regional lymphadenopathy. Various ocular manifestations of cat scratch disease have been described, mainly retinochoroiditis, optic disc swelling, neuroretinitis, vascular occlusive events, serous retinal detachment, vitreous hemorrhage, intermediate uveitis, inflammatory lesions of the optic nerve head and rarely full thickness macular hole. We describe a case of an 11-year-old girl who presented 2 weeks after the onset of symptoms, with B. Henselae neuroretinitis with full thickness macular hole at presentation.